PENINGKATAN PENGETAHUAN DAN KETERAMPILAN IBU HAMIL MENGENAI GIZI DAN SUMBER PANGAN LOKAL UNTUK PENCEGAHAN STUNTING DI KAMPUNG NOTOHARJO KECAMATAN TRIMURJO KABUPATEN LAMPUNG TENGAH - Yuniastini, Yuniastini; Yulida Fithri; Rifai Agung Mulyono; Suryani Catur S (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2025)
Pregnant women's knowledge about nutritional needs during pregnancy is very important to improve maternal and fetal health and prevent stunting. This will be even more meaningful if it is complemented by the mother's skills in utilizing local food sources as an affordable nutritional solution. Therefore, combining activities to educate mothers while providing direct practice is a good choice and suits the needs of pregnant women. This is the background to the community service activities of lecturers and students at the Tanjungkarang Health Polytechnic in Notoharjo village, Trimurjo district, Central Lampung. This activity involves direct practice in the form of introducing local food sources, using the KIA Book as a source of knowledge, and making soy milk as an alternative source of protein. The results of the activity showed an increase in pregnant women's understanding of daily nutritional needs and skills in practicing nutritional knowledge. This activity shows that community-based education involving local food sources has the potential to increase pregnant women's awareness of the importance of balanced and affordable nutrition to prevent stunting